Effects of intramuscular injection of artemether® on the histology of the uterus and ovaries of pregnant wistar rats - A. Tijani, A.; A. Adekomi, D. (Scientific Journal of Medical Science, 2012)
This experiment was aimed at studying some of the histological effects of Artemether® on the uterus and ovaries of pregnant Wister Rats. Twelve pregnant rats were divided equally into treated and control groups. The rats in treated group received Artemether® while those in control group received phosphate buffered saline. Administration was intramuscular. Macroscopically, no significant differences were observed in the organs extracted in the treated and control rats. Microscopically, there is thick uterine mucosa with edematous gland and stroma with developed follicle in the ovaries of treated rats as observed 72 hours after intramuscular administration of Artemether®. The results of this study showed that administration of Artemether® intramuscularly to pregnant Wistar rats caused embryo loss.